Institutional factors and economic policy uncertainty: An asymmetric analysis - YILDIZ, Tuba; KIRMIZIOĞLU, Hale; ARSLAN, Ünal; ÇELİKÖZ, Yıldız SAĞLAM (Edelweiss Applied Science and Technology, 2025)
This study examines the relationship between economic policy uncertainties and institutional infrastructure or institutional quality. Countries with strong institutional quality may reduce economic policy uncertainty. In the effectiveness of this situation, it is particularly important that well-functioning institutions make economic decision-making processes more predictable, stable, and reliable. Institutional quality can help build confidence, stability, and predictability in the economy. This condition may decrease economic policy uncertainty, resulting in improved growth and prosperity. Strong institutional quality in European Union countries may additionally serve to promote long-term growth by lowering economic policy uncertainty. In the study, the effect of economic policy uncertainty was analyzed using the ARDL nonlinear analysis method and data from eight European countries for the period 2002-2021. As a result of the analysis, it was concluded that there is an asymmetric relationship between corruption control and economic policy uncertainty. Negative shocks to the quality of regulation positively affect economic policy uncertainty. Positive shocks to voice, accountability, political stability, and the absence of violence positively affect economic policy uncertainty.